Tangram e resolução de problemas: Desafios e possibilidades - Costa, Sídney Moreira da (2019)
This research aims to reflect on the challenges and possibilities from the Tangram associated to the solving problems, with the attention to their exploration and proposition. To achieve this purpose, we try to answer to the following questions: How the textbooks explore the Tangram and the solving problems? What are the potentialities and difficulties to use the methodology in the solving problems in the use of the Tangram in classroom? The study with a qualitative aspect will search to understand the phenomenon in its totality and will be search for significant comprehensions and interpretations about the studied object. The data collection was performed through the analysis of textbooks by the sense categories that were created by the regularities noticed and the interviews with the teachers from the most variates sectors of education, since the childhood to the higher education. The interviews were analyzed using the Discourse of Collective Subject DCS - (LEFÊVRE; LEFÊVRE, 2015) methodology that help us to reveal what the collectivity reflects. The workshop help us to link the theory and the practice in order to develop considerations about the use of Tangram when it is allied to the solving, exploration and proposition of problems. Then the date appreciation, it was found that the teachers recognize the possibilities about the use of Tangram and that the when it is associated to the solving problems, the use of Tangram may promote the students‘ motivation, the comprehension about the mathematical concepts, the development of autonomy and creativity. Furthermore, the professors pointed as challenges the need of the well-defined objectives formulation and an appropriate methodology in the classes, the difficulty in solving problems by the students as well as the lack of teachers training what impedes the development of winning experiences in Math classes when the use of Tangram is associated to the solving problems.